Zirconium in the Nuclear Industry: Tenth International Symposium 1994
DOI: 10.1520/stp15212s
|View full text |Cite
|
Sign up to set email alerts
|

Examinations of the Corrosion Mechanism of Zirconium Alloys

Abstract: Several mechanism-related aspects of the corrosion of zirconium alloys have been investigated using different examination techniques. The microstructure of different types of oxide layers was analyzed by transmission electron microscopy (TEM). Uniform oxide mainly consists of m-ZrO2 and a smaller fraction of t-ZrO2 with columnar grains and some amount of equiaxed crystallites. Nodular oxides show a high open porosity and the grain shape tends to the equiaxed type. A fine network of pores along grain boundaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 14 publications
5
52
0
Order By: Relevance
“…Various experimental studies have demonstrated an increased fraction of the non-equilbrium tetragonal phase close to the metal-oxide interface [3,4,5], where it is stabilised by a combination of i) small grain size, ii) compressive stress (from the Pilling-Bedworth ratio of 1.56 on transformation from α-Zr to ZrO 2 ) and iii) the inclusion of alloying elements as dopants incorporated into the growing oxide layer [6,7,8]. As corrosion progresses, the metal/oxide interface (the point at which the electrochemical reaction takes place [8,9]) moves away from the newly formed oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental studies have demonstrated an increased fraction of the non-equilbrium tetragonal phase close to the metal-oxide interface [3,4,5], where it is stabilised by a combination of i) small grain size, ii) compressive stress (from the Pilling-Bedworth ratio of 1.56 on transformation from α-Zr to ZrO 2 ) and iii) the inclusion of alloying elements as dopants incorporated into the growing oxide layer [6,7,8]. As corrosion progresses, the metal/oxide interface (the point at which the electrochemical reaction takes place [8,9]) moves away from the newly formed oxide.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable research about the oxide layer including its microstructure [1][2][3], crystallographic structure [4,5], stress distribution [6][7][8], and hydrogen diffusivity [9][10][11][12]. Transmission electron microscopy observations revealed that oxide layers near metal/oxide interfaces include tetragonal zirconium oxide [4,5], which is metastable at the cladding temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy observations revealed that oxide layers near metal/oxide interfaces include tetragonal zirconium oxide [4,5], which is metastable at the cladding temperature and pressure. This implies that the oxide layer is subjected to a high compressive stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tetragonal structure can be stabilized in the corrosion process of the Zr alloys. The mechanism of the stabilization of the tetragonal phase in the oxide can be explained in several ways such as the high compressive stress in the oxide, the small grain size or the presence of the point defect [11,[17][18][19][20][21][22]. Godlewski et al obtained the distribution of the tetragonal phase fraction in the oxide by a Raman spectros- copy and clarified that the tetragonal fraction is usually higher in the interface region than in the surface region in the oxide [23].…”
Section: Characterization Of the Oxidementioning
confidence: 99%